Public Perception of Disability: Promoting Awareness Through Education and Social Interaction - Moch Salman Achyar; Endang Pudjiastuti Sartinah; Nur Rawaidah Rahma; Rizki Buana Dewi (Yayasan Darussalam Bengkulu, 2026)
This study examines public perceptions toward people with disabilities and the critical need to increase awareness for inclusive environments in Indonesia. A descriptive quantitative survey was conducted involving 366 young adult respondents. The instrument's validity and reliability were statistically confirmed (p < 0.001). The structured questionnaire focused on social interaction frequency, emotional comfort, perceptions of equal opportunities, and the role of formal education. The results show that while respondents generally demonstrated positive interpersonal attitudes and comfort (42%), a significant portion still perceived systemic inequality in educational and employment opportunities (37%). Most notably, the majority of respondents (67%) considered formal education highly insufficient in promoting disability awareness. These findings highlight the urgent need to strengthen inclusive educational curricula and facilitate meaningful social interactions to bridge the gap between individual acceptance and structural equality.